Pauli Exclusion Classical Potential for Intermediate-Energy Heavy-Ion Collisions - Dorso, Claudio Oscar (2023)
This article presents a classical potential used to describe nucleon–nucleon interactions at intermediate energies. The potential depends on the relative momentum of the colliding nucleons and can be used to describe interactions at low momentum transfer mimicking the Pauli exclusion principle. We use the potential with molecular dynamics to study finite nuclei, their binding energy, radii, symmetry energy, and a case study of collisions.